- Thread starter
- #1

#### DeusAbscondus

##### Active member

- Jun 30, 2012

- 176

by what rule of differentiation does the constant '4' in the following expression, get included, unmodified, in the differentiation

$$y=4cos(x^3-2x) \Rightarrow y'=-4(3x^2-2).sin(x^3-2x)$$

A cross-wire in my mind wants to apply the rule:

$$y=c\Rightarrow y'=0, where, c=constant$$

Incidentally, I've searched and searched and can't find an explanation as to the logical/operational difference between the following:

$\Rightarrow$ and $\rightarrow$

Please explain,

thanks again (hellow Sudharaka)

DeusAbs